A novel non-linear model-based control strategy to improve PEMFC water management – The flatness-based approach. (9th February 2015) - Damour, Cédric; Benne, Michel; Grondin-Perez, Brigitte; Chabriat, Jean-Pierre; Pollet, Bruno G.
Abstract In the area of PEMFC, water management and thus membrane humidity still remains one of the most challenging issues affecting PEMFC efficiency and lifetime. In this investigation, an innovative method to improve PEMFC water management is presented and a non-linear model-based control strategy is proposed. The novelty of this approach relies upon a simplified PEMFC model combining the benefits of the Differential Flatness Theory. Efficiency and relevance of the proposed water management strategy is confirmed in simulation environment through several controlled scenarios. It was found that in each case, the flatness-based controller successfully regulates the membrane humidity, while avoiding flooding or even membrane drying that can lead to irreversible damage. Furthermore, the novel model demonstrates excellent performance in terms of set-point tracking, disturbances rejection and robustness against parameters uncertainties and measurement noise. Overall, this novel approach appears to be a possible and promising towards improving PEMFC water management issues.